Determinants of credit access of cocoa farmers - Oppong Mensah, Nicholas; Yeboah, Edward; Donkor, Anthony; Osei Tutu, Frank; Kaanye Dier, Richard (Applied Studies in Agribusiness and Commerce, 2019)
Access to credit is one of the critical areas that are of prime interest to development practitioners, agribusiness entrepreneurs and agricultural economists, mainly access to credit by farmers in order to increase their production and also reduce poverty. This study sought to analyze the determinants of credit access among cocoa farmers in the Asunafo North of the Ahafo Region of Ghana. The multistage sampling procedure was used to collect data from 100 cocoa farmers with the aid of a questionnaire. Sources of credit, factors influencing access to credit, and constraints to credit were analyzed with the aid of descriptive statistics, multiple linear regression, and Kendall’s coefficient of concordance respectively. The results of multiple linear regression revealed that, age, marital status, education, experience, and family size were significant factors that influenced access to credit. The constraints analysis with the aid of Kendall’s coefficient of concordance showed that, high interest rate was highly ranked with a mean score of 1.93 whilst the need for a guarantor was least ranked with a mean score of 7.40. Based on the results, the study recommended that a policy aimed at expanding formal and semi-formal financial institutions credit portfolio to embrace cocoa farmers by finding alternative to collaterals and also reducing the interest rate will improve credit access with a positive externality effect of poverty reduction among cocoa farmers in the study area. JEL Classification: Q14